Antesenden Kepercayaan Pasien Dengan Mediasi Kepuasan Pasien: Rekfleksi Dari Good Governance - Sudarmini, Ni Luh Putu; Gorda, A.A.N. Oka Suryadinatha; Subanda, I Nyoman (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2022)
The public's need for health services such as hospitals or clinics continues to increase day by day. This is due to the maturity factor of people's thinking which is currently thinking critically about health services in general. This study aims to examine and develop the variables that underlie patient trust that comes from the quality of service and caring behavior of medical personnel by mediating patient satisfaction in the health services of the Klungkung Regency Government, Bali Province. This location was chosen because Klungkung Regency has a more innovative service unit program called PSC Kris which is in charge of picking up patients to be referred to government health service centers such as hospitals or health centers. This research design uses a descriptive quantitative approach using four main variables, namely Caring Behavior; Service Quality, Patient Satisfaction and Patient Trust. The research instrument used an open questionnaire with an interval scale of 1-10. The sample used in this study used a stratified random sampling technique with a total of 148 respondents. Data analysis in this study used the SEM method assisted by the Smart PLS 3.2 program. The results showed that the quality of service gave a positive and significant influence partially on patient trust, and had a positive and significant influence indirectly through patient satisfaction variables. While the rejection of the influence of caring behavior both passively and mediated by patient satisfaction. This is caused by medical personnel who still lack care in providing health services. The results of the study can be used by the Klungkung District Health Office to be able to evaluate and improve the caring behavior of medical personnel in providing health services to the community.